Fatal Zika virus infection in the Americas: A systematic review. (November 2019) - Cardona-Ospina, Jaime A.; Henao-SanMartin, Valentina; Acevedo-Mendoza, Wilmer F.; Nasner-Posso, Katherinn Melissa; Martínez-Pulgarín, Dayron F.; Restrepo-López, Abril; Valencia-Gallego, Valentina; Collins, Matthew H.; Rodriguez-Morales, Alfonso J.
Highlights: Severe manifestations of Zika virus (ZIKV) infection have recently been noted during epidemics. A systematic review of the literature was performed, showing 51 reported deaths associated with ZIKV infection in nine countries, the majority (56.9%) not related to Guillain–Barré syndrome. Cases from the Dominican Republic, Brazil, and Puerto Rico accounted for 67.6% of the deaths (33.3%, 18.6%, and 15.7%, respectively). ZIKV infection in the majority of cases (64.7%) was confirmed by RT-PCR, MAC-ELISA, or immunohistochemistry. An increasing number of fatalities have been published in the literature since the first death was reported in 2016; however, additional research is needed to elucidate factors that may mediate the pathogenesis of severe, atypical, and fatal disease. Abstract: Introduction: While death due to Zika virus (ZIKV) infection has been described, reports of fatal cases have been infrequent and no systematic reviews on the subject have been published. Methods: A systematic review of the literature in four databases was performed to assess fatal outcomes of postnatal ZIKV infection and the available evidence that links ZIKV infection to death. Results: Three hundred and eleven articles were retrieved; 20 of them were epidemiological reports from surveillance agencies and ministries of health. After screening by abstract and title, 59 articles were selected for full-text assessment. Of these, 35 were excluded (with reasons) and 24 were finally included for qualitative analysis. A total of 51 reported deaths associated with ZIKV infection in nine countries were identified. The majority of cases (56.9%) were not related to Guillain–Barré syndrome. Cases from three countries accounted for 67.6% of the deaths. ZIKV infection was laboratory-confirmed in the majority of cases (64.7%). Discussion: ZIKV was not considered to be a dangerous, and much less a lethal pathogen, until very recently. However, an increasing number of fatalities have been published in the literature since the first death was reported in 2016. Additional research is needed to elucidate factors that may mediate the pathogenesis of severe, atypical, and fatal disease.